Implementation of Inclusion Education in the Madrasah Ibtidaiyah Keji, West Ungaran, Semarang - Nofiaturrahmah, Fifi; Kusmiyarsih, Sri (Pascasarjana IAIN Kudus, 2023)
Inclusive education in madrasas still requires special attention from the Ministry of Religion to continue to grow and increase in line with the need to accept children with special needs in madrasas because, so far, inclusive education is still dominated by general education institutions. This study aims to identify and analyze the implementation of inclusive education at MI Keji Ungaran Barat. The research method uses qualitative research, data collection techniques use the method of observation, interviews, documentation, data triangulation, data analysis techniques using the theory of Miles and Huberman, then validated the validity of the data for the credibility test, dependability test, confirmability test, and transferability test with data analysis techniques, data reduction, data presentation and verification (Conclusion drawing). The research resulted in a description and analysis: the implementation of inclusive madrasah education includes the preparation of an inclusive education support system in madrasas, acceptance of students with special needs, identification and assessment of students with special needs, empowerment of teachers and education personnel, curriculum accommodation and implementation of individual education program learning, outcome assessment learning, fulfilling the need for facilities and infrastructure to support inclusive education, establishing partnerships and building inclusive education networks. Implementasi Pendidikan Inklusi di Madrasah Ibtidaiyah Keji Ungaran Barat Semarang. Pendidikan inklusi di madrasah masih memerlukan perhatian khusus dari Kementerian Agama agar bisa terus berkembang dan bertambah seiring dengan kebutuhan penerimaan anak berkebutuhan khusus di madrasah karena selama ini pendidikan inklusi masih didominasi oleh lembaga pendidikan umum. Penelitian ini bertujuan untuk mengetahui dan menganalisis pelaksanaan pendidikan inklusi di MI Keji Ungaran Barat. Metode penelitian menggunakan penelitian kualitatif, teknik pengumpulan data menggunakan metode observasi, wawancara, dokumentasi, triangulasi data. Teknik analisis data menggunakan teori Miles dan Huberman kemudian dilakukan validasi keabsahan data uji kredbilitas, uji dependability, uji comfirmability dan uji transferability dengan teknik analisis data, reduksi data, penyajian data dan verifikasi (Conclusion drawing).Penelitian menghasilkan deskripsi dan analisis: pelaksanaan pendidikan madrasah inklusimeliputi penyiapan sistem pendukung pendidikan inklusi di madrasah, penerimaan peserta didik berkebutuhan khusus, identifikasi dan assesmen peserta didik berkebutuhan khusus, pemberdayaan guru dan tenaga kependidikan, akomodasi kurikulum dan pelaksanaan pembelajaran program pendidikan individual, penilaian hasil belajar, pemenuhan kebutuhan saranadan prasaranan penunjang pendidikan inklusi, menjalin kerjasama kemitraan dan membangun jaringan pendidikan inklusi.